Application of response surface methodology in evaluating the performance of conventional, wiper, cryogenically treated and coated (TiN, TiAlN and TiCN) carbide inserts in turning of AISI 52100 steel. (2018) - Pradeep, A.V.; Lingaraju, D.; Ramakrishna, S.
The performance of untreated/uncoated, wiper, deep cryogenically treated, and coated (TiN, TiAlN and TiCN) carbide inserts using response surface methodology in turning of AISI 52100 steel, was evaluated in this study. Type of insert, cutting speed, feed and depth of cut were the factors investigated. The response variables analysed were tool flank wear and surface roughness. Basing on RSM central composite design, an experimental plan (L18 OA) was developed. The ANOVA results signify that the suggested mathematical models could adequately elucidate the performance indicators within the range. The generated regression equation reveals that the flank wear is mainly influenced by the type of insert followed by cutting speed. The surface roughness was majorly affected by the type of insert followed by feed rate. Machined surface topographies and tool flank wear mechanism were analysed by examining the SEM micrographs. RSM multi-response optimisation was executed so as to optimise the turning parameters.